Epidural versus intravenous steroids application following percutaneous endoscopic lumbar discectomy. Issue 18 (May 2018) - Hu, Annan; Gu, Xin; Guan, Xiaofei; Fan, Guoxin; He, Shisheng
Abstract : Abstract: Retrospectively study. The purpose of this study was to compare the effects of intraoperative epidural steroids and single dose intravenous steroids following a percutaneous endoscopic lumbar discectomy (PELD). Inflammatory irritation of dorsal root ganglia or sensory nerve roots may cause postoperative pain. Epidural steroids have been applied after a lumbar discectomy for more than 20 years. Epidural steroid application after a PELD is easier to perform and safer because the operations are under observation of the scope. We retrospectively reviewed the medical records of patients with lumbar intervertebral disc herniation who had undergone transforaminal PELD at our department. There are 60 patients in epidural steroid group, intravenous steroid group, and control group, respectively. Visual analog scores (VAS) and the Oswestry Disability Index (ODI) were collected. Successful pain control is defined as 50% or more reduction in back and leg pain (VAS scores). VAS scores (back and leg) and ODI showed a significant decrease in all groups when comparing pre- and postoperatively. Epidural steroid group had a significant improvement in successful pain control compared with the control group at 2 weeks of follow-up. VAS scores (leg) in the epidural steroid group showed a significant decrease compared with the intravenous steroids group at 1, 3, and 7 days after the surgery, but this difference had no statistical significance at 1, 6, and 12 months of follow-up. All groups did not show a significant difference in ODI at 1, 6, and 12 months follow-up. Epidural application of steroid has a better effect on controlling the postoperative pain of PELD in the short term. The epidural application of steroid did not show a tendency to cause infection.